Microplastic contamination in green mussel aquaculture at straits of Johor - Maha, Raihana Rozan (2019)
Microplastics are anthropogenic pollutants present in various morphology of less than 5 mm in diameter. Primary microplastics are manufactured in the form of microbeads and synthetic fibre used in various product. Meanwhile, secondary microplastic resulted from the breaking down of larger plastic material into smaller fragments. The widespread of microplastic contamination in marine environment creates a concern on its impact toward the food chain. In this study, microplastic contamination in seawater and farmed green mussel (Perna viridis) at Strait of Johor was investigated. Result from the investigation showed a positive contamination of microplastic in seawater and green mussel samples from the aquaculture sampling location. On average, microplastics present in green mussel samples collected from Kampung Pasir Putih was 0.58 ± 0.25 items/g and 1.95 ± 1.14 items/individual. Meanwhile, the abundance of microplastic in seawater samples was 8 ± 3.85 items/L. Fibres were the most common microplastic followed by fragments, with various size and colour. The result from this study can be used as a baseline level of microplastic contamination in green mussel aquaculture located at Straits of Johor. It is a concern that the presence of microplastic in seafood might bring negative consequences to human health. Therefore, intensive assessment of microplastic contamination in seafood should be conducted for better understanding on the impacts as well as for future reference.